Debate: Bipolar disorder: extremely rare before puberty and antipsychotics cause serious harms – a commentary on Van Meter et al. (2019). Issue 1 (28th January 2019) - Parry, Peter; Allison, Stephen; Bastiampillai, Tarun
Abstract : 'Paediatric bipolar disorder' (PBD) remains controversial; because it is based on the hypothesis that bipolar disorder (BD) often begins in childhood with atypical forms of mania. A meta‐analysis of 12 epidemiological surveys found a high prevalence of PBD among children and adolescents worldwide (1.8%), however, our study of the measurement issues (Child and Adolescent Mental Health, 23, 2018, 14) found that PBD rates were lower than claimed. Our findings are consistent with the developmental trajectory of BD, as described by most longitudinal studies of high‐risk offspring. BD is extremely rare in childhood with nearly all index manic/hypomanic episodes being in midadolescence or later. Treatment for BD should not commence until the first well‐defined manic/hypomanic episode, because children and younger adolescents are extremely sensitive to the side effects of second‐generation antipsychotics including weight gain, metabolic syndrome, extrapyramidal side effects and the risk of cerebral atrophy, as observed in studies of juvenile animals. Abstract : Read the Editors' introduction at: doi: 10.1111/camh.12315 Read the core debate at: doi: 10.1111/camh.12231 ; doi: 10.1111/camh.12243 ; doi: 10.1111/camh.12296 Read more perspectives in this debate at: doi: 10.1111/camh.12318 doi: 10.1111/camh.12317 ; doi: 10.1111/camh.12316 ; doi: 10.1111/camh.12313 ; doi: 10.1111/camh.12310 ; doi: 10.1111/camh.12314